(untitled) (Pragyaratna प्रज्ञारत्न, 2025)
This study addresses a critical gap in climate governance literature by investigating the empirical relationship between public climate finance and environmental outcomes in Nepal, a country highly vulnerable to climate change despite its minimal historical emissions. Using a correlational research design with a one-year lag, we analyze ten years of national data (2014-2023) to determine whether Nepal’s total climate-relevant budget (TCB) and its environment-sector share (ESB) are associated with changes in per-capita greenhouse gas emissions. Our analysis reveals a paradox: a very strong positive correlation between the rapidly expanding TCB and rising emissions, whereas a greater ESB shows a negative, though statistically weaker, association. The findings indicate that the scale of spending alone is an inadequate strategy for mitigation; instead, effectiveness is contingent upon strategic budget composition, prioritizing interventions with verifiable abatement potential, and overcoming systemic implementation bottlenecks. The primary implication for policy and practice is the necessity of a decisive pivot from quantitative expansion to qualitative targeting, establishing a mitigation-sensitive budgeting framework that directly links allocations to measurable emissions reductions through enhanced delivery systems and verification.